Efektivitas atau Aksesibilitas: Kajian Desain Mal Pelayanan Publik dalam Perspektif Desain Inklusi - Moh Syahru Romadhon Sholeh; I Gusti Ngurah Antaryama; Vincentius Totok Noerwasito (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
The SDG's primary target of providing an inclusive environment has a lot to do with the quality of public services. However, in terms of infrastructure, there are still various shortcomings, especially in implementing designs based on inclusive design.  Malang City, one of the cities with new public service facilities, chose an existing building to become a public service mall. Issues that occur include unfriendly circulation, inappropriate space functions and not adequately accommodated mobility of users with special needs, elders and children because there is only one access. This research uses a qualitative approach with observation and interviews as a method and the principle of inclusive design as a research tool. The result of the study from this research is that the Mal Pelayanan Publik Merdeka Kota Malang has not yet become an inclusive public facility.